PH, solvent and metal ion induced octamolybdate-based metal–organic complexes decorated with a pyridyl-carboxylate ligand containing an amide group. Issue 6 (14th January 2016) - Wang, Xiuli; Liu, Danna; Lin, Hongyan; Liu, Guocheng; Wang, Xiang; Le, Mao; Rong, Xing
Abstract : Three octamolybdate-based metal–organic complexes constructed from a pyridyl-carboxylate ligand containing an amide group and different central metal ions have been hydrothermally/solvothermally synthesized and characterized. Abstract : Three octamolybdate-based metal–organic complexes constructed from a pyridyl-carboxylate ligand containing an amide group, 3-(2-pyridinecarboxylic acid)amido pyridine (HPCAP), namely, H2 [Cu3 (PCAP)4 (H2 O)2 ](β-Mo8 O26 )·10H2 O (1 ), H[Cu(PCAP)(H2 O)](β-Mo8 O26 )0.5 (2 ) and H2 [Co(H2 O)6 ][Co2 (PCAP)4 (γ-Mo8 O26 )(H2 O)2 ]·10H2 O (3 ), have been successfully synthesized under hydrothermal or solvothermal (methanol–water mixed solvent) conditions. Single-crystal X-ray analyses reveal that compound1 is a 2D layer based on infinite 1D [Cu3 (PCAP)4 ] n 2 n + chains and bidentate β-Mo8 O26 4− anions. In compound2, 1D "thin centipede" [Cu2 (PCAP)2 ] n 2 n + chains were connected by tetradentate β-Mo8 O26 4− anions through the Cu–O bond to form a 2D network. In compound3, γ-Mo8 O26 4− anions were connected by adjacent [Co2 (PCAP)4 (H2 O)2 ] moieties through Co–O and Mo–N bonds forming an uncommon 1D "fat centipede" chain. The adjacent chains were further extended to a 2D supramolecular network through hydrogen bonding interactions. The title compounds represent the first examples of introducing a pyridyl-carboxylate ligand containing an amide group into the POM system. The pH value, solvent and metal ions play key roles in the construction of the final architectures and show a great influence on the structural diversities of the title compounds. The electrochemical properties of compound1 and the photocatalysis properties of the title compounds have been reported.